2021
DOI: 10.1097/pcc.0000000000002735
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Errors in Pediatric Critical Care: A Systematic Review*

Abstract: Studies on diagnostic error and the diagnostic process in pediatric critical care were included. Non-English studies with no translation, case reports/series, studies providing no information on diagnostic error, studies focused on non-PICU populations, and studies focused on a single condition/disease or a single diagnostic test/tool were excluded.DATA EXTRACTION: Data on research design, objectives, study sample, and results pertaining to the prevalence, impact, and factors associated with diagnostic error w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…A systematic review in Pediatric Critical Care found that up to 67% of diagnostic errors in the pediatric critical care setting are related to system factors, while up to 30% included cognitive factors. Notably, 40% of the diagnostic errors combined cognitive and system factors [61].…”
Section: Common Errorsmentioning
confidence: 99%
“…A systematic review in Pediatric Critical Care found that up to 67% of diagnostic errors in the pediatric critical care setting are related to system factors, while up to 30% included cognitive factors. Notably, 40% of the diagnostic errors combined cognitive and system factors [61].…”
Section: Common Errorsmentioning
confidence: 99%
“…MOID is thought to be frequent and associated with negative outcomes in pediatric and adult hospital settings. 10,[13][14][15] However, identifying MOID can be challenging and resourceintensive, which limits the potential for using MOID to inform systems learning and improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnostic errors, commonly referred to as “missed opportunities to improve diagnosis” (MOID), are defined as missed opportunities to make the correct or timely diagnosis. MOID is thought to be frequent and associated with negative outcomes in pediatric and adult hospital settings 10,13–15 . However, identifying MOID can be challenging and resource‐intensive, which limits the potential for using MOID to inform systems learning and improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Up to 70% of all medical decisions are based on laboratory tests [5]. Furthermore, diagnostic errors contribute to about 10% of patients' death and close to 17% of hospital complications [6]. To address these challenges, many researchers and organizations are working on introducing machine learning to diagnostic applications to improve the speed and accuracy of diagnosis which will produce results that are similar to previous applications of diagnoses as well as improve the reliability of the process [7].…”
Section: Introductionmentioning
confidence: 99%